Multi-criteria decision making techniques in successful knowledge sharing behaviour among Malaysian student - Sulaiman, Nor Intan Saniah; Mohd Sappri, Mazlan; Md Ali, Khodijah (2012)
This research was identified the success determinants of knowledge sharing behaviour (KSB) among Malaysian university students (MUS).Each university has their own method in delivering knowledge to their undergraduates, but occasionally there would still be incomplete or hidden information. The research question is: what are the success factors in knowledge sharing behaviour (KSB) among Malaysian undergraduate communities in one of northern university in Malaysia? The aim of this research is to identify the success factors for effective knowledge sharing behaviour (KS) among Malaysian university students (MUS) in one of northern university in Malaysia.The identification was done through multi-criteria decision making techniques, which are Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS) and Ranked Base on Percentage.Both techniques has come out with same result, where the personal contributes as success factors in knowledge sharing behaviour among undergraduate students.